Spontaneous porto‐femoral shunting in long‐standing portal hypertension. Issue 9 (25th May 2020) - Giuffrè, Mauro; Martingano, Paola; Crocè, Lory Saveria
Abstract: Spontaneous portosystemic shunting is a compensation mechanism that is supposed to relieve the portal circulation from high pressures. Here we report an unusual shunt that originates from a patent paraumbilical vein and reaches the femoral vein via the inferior epigastric vein. Despite being merely anecdotal, this finding is fascinating from an anatomical point of view. Abstract : Spontaneous portosystemic shunting is a compensation mechanism that is supposed to relieve the portal circulation from high pressures. Here we report an unusual shunt that originates from a patent paraumbilical vein and reaches the femoral vein via the inferior epigastric vein. Despite being merely anecdotal, this finding is fascinating from an anatomical point of view.